Work Agreement on Outsourcing System and Legal Protection for Workers - Retno Widyorini, Sri; Tyaswati WL, Aniek (International Journal of Educational Research & Social Sciences, 2022)
The outsourcing work system is expected to provide legal protection for workers. The status of the employment relationship between the worker and the employer is stated in the Employment Agreement (SPK). The purpose of this study is to determine the advantages of implementing an outsourcing work contract model for companies, legal protection for workers with an outsourcing work contract model, and the efforts that the government has made in anticipating the emergence of industrial relations disputes between outsourced workers and labor supply companies and employers' companies. The method used is normative juridical, using secondary data as the primary data as supporting data. Secondary data was obtained by conducting a literature study through literature and legislation. The analysis was carried out qualitatively. The results of this study found that for companies to cost of production efficiency (cost of production), the government hopes to provide benefits to develop and encourage community economic growth and national economic growth. In the practice of outsourcing, wage discrimination often occurs between permanent workers who work for the principal company (employer company) and outsourcing workers (contract workers), continuing work with a contract work system. Protection for workers is provided by the existence of labor law because, by law, it means that there is a state guarantee to provide decent work to protect it in the workplace, such as health, work safety, and living wages. Apart from that, it is also up to the provision of social security after retirement, through trade unions or labor unions, providing legal assistance in case of problems, both in terms of non-judicial legal remedies and judicial legal efforts.